Overview on the Trojan Horse Method in nuclear astrophysics. (December 2020) - Lamia, L.; Pizzone, R.G.; Mazzocco, M.; Hayakawa, S.; Cognata, M. La; Bertulani, C.A.; Cherubini, S.; D'Agata, G.; Guardo, G.L.; Gulino, M.; Indelicato, I.; Rapisarda, G.G.; et al.
Abstract: The use of the Trojan Horse Method (THM) appears as one of the most suitable tools for investigating nuclear processes of interest for astrophysics. THM has been demonstrated to be useful for exploring different nuclear reactions intervening both in stellar and primordial nucleosynthesis as well. Some recent results will be here discussed together with a brief discussion of the fundamental theoretical description. General details about the recently studied 7 Be(n, α ) 4 He reaction will be given.